#DeactivHate: An Educational Experience for Recognizing and Counteracting Online Hate Speech - Alessandra Teresa Cignarella; Simona Frenda; Mirko Lai; Viviana Patti; Cristina Bosco (IJCoL)
The possibility of raising awareness –especially in young generations– about misbehavior online such as hate speech, could help society to reduce its impact, and thus, its negative consequences. In the last years, the Computer Science Department of the University of Turin has designed various technologies that support educational projects and activities in this perspective. In this paper, we describe the creation of a laboratory called #DeactivHate, specifically designed for secondary school students. The laboratory aims at countering hateful phenomena online and making students aware of technologies that they use on a daily basis. We describe the teaching experience of the first year of life of the laboratory held in different high school classes between April 2021 and March 2022 and the outcomes of the technologies and activities tested. In this extended version of the paper, some sections are especially devoted to observe and analyze the impact of the course on students and their perspective on the laboratory.